Pengaruh Kurs Dollar, Indeks Dow Jones dan Tingkat Suku Bunga Sertifikat Bank Indonesia (SBI) Terhadap Indeks Harga Saham gabungan (IHSG) (Periode 2016-2018) - Sri Puspa Nurhayati; Ronny Malavia Mardani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe capital market is one investment alternative for investors.  Investors who are willing to invest in the stock market can invest in the Indonesia Stock Exchange (BEI). One index that is often ignored by investors when they invest in the Indonesia Stock Exchange is the Composite Stock Price Index (CSPI), because through the movement of the Composite Stock Price Index, investors can see whether the market conditions are excited or sluggish. Some things that need to be considered by investors in investing are the dollar exchange rate, dow jones index and the interest rate of Bank Indonesia certificates, This study aims to test and empirically prove the effect of the exchange rate of the dollar, the Dow Jones index, and the interest rate of Bank Indonesia certificates on the composite stock price index during the period January 2016 to December 2018. The sampling technique used in this study is purposive sampling with the amount  144 data were processed. The analyzed data were carried out using multiple linear regression methods. The results showed that the Dollar Exchange Rate variable had a significant positive effect on the Composite Stock Price Index (CSPI).  SBI Interest Rate has a significant negative effect on the composite stock price index (CSPI).Keywords: Composite Stock Price Index (CSPI), Dollar Exchange Rate, Dow Jones Index, Bank Indonesia Certificate Interest Rate.